Deletion of the nicotinic acetylcholine receptor subunit gene Dα1 confers insecticide resistance, but at what cost?. Issue 1 (2nd January 2018) - Somers, Jason; Luong, Hang Ngoc Bao; Batterham, Philip; Perry, Trent
ABSTRACT: Nicotinic acetylcholine receptors (nAChRs) have vital functions in processes of neurotransmission that underpin key behaviors. These pentameric ligand-gated ion channels have been used as targets for insecticides that constitutively activate them, causing the death of insect pests. In examining a knockout of the Dα1 nAChR subunit gene, our study linked this one subunit with multiple traits. We were able to confirm previous work that had identified Dα1 as a target of the neonicotinoid class of insecticides. Further, we uncovered roles for the gene in influencing mating behavior and patterns of sleep. The knockout mutant was also observed to have a significant reduction in longevity. This study highlighted the severe fitness costs that appear to be associated with the loss of function of this gene in natural populations in the absence of insecticides targeting the Dα1 subunit. Such a fitness cost could explain why target site resistances to neonicotinoids in pest insect populations have been associated specific amino acid replacement mutations in nAChR subunits, rather than loss of function. That mutant phenotypes were observed for the two behaviors examined indicates that the functions of Dα1, and other nAChR subunits, need to be explored more broadly. It also remains to be established whether these phenotypes were due to loss of the Dα1 receptor and/or to compensatory changes in the expression levels of other nAChR subunits.